Long-term evolution of luminescent properties in CdI2 crystals - Karbovnyk, I.; Bolesta, I.; Rovetskyi, I.; Lesivtsiv, V.; Shmygelsky, Ya.; Velgosh, S.; Popov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Fresh and aged melt-grown or gas-phase grown CdI2 crystals are studied by means of low-temperature photo-luminescence spectroscopy. Noticeable transformations of emission spectra are observed after long-term aging. The formation of nanostructures containing cadmium oxide and cadmium hydroxide as well as the changes in local surrounding of iodine atoms and the possible growth of polytypic modifications of CdI2 are taken into account when considering the diversity of optical spectra.